A Heterochromatic Knob Reducing the Flowering Time in Maize - Carvalho, Renata Flávia; Aguiar-Perecin, Margarida Lopes Rodrigues; Clarindo, Wellington Ronildo; Fristche-Neto, Roberto; Mondin, Mateus (Frontiers in Genetics, 2022)
Maize flowering time is an important agronomic trait, which has been associated with variations in the genome size and heterochromatic knobs content. We integrated three steps to show this association. Firstly, we selected inbred lines varying for heterochromatic knob composition at specific sites in the homozygous state. Then, we produced homozygous and heterozygous hybrids for knobs. Second, we measured the genome size and flowering time for all materials. Knob composition did not affect the genome size and flowering time. Finally, we developed an association study and identified a knob marker on chromosome 9 showing the strongest association with flowering time. Indeed, modeling allele substitution and dominance effects could offer only one heterochromatic knob locus that could affect flowering time, making it earlier rather than the knob composition.